Novel sulphonamide-bearing methoxyquinazolinone derivatives as anticancer and apoptosis inducers: synthesis, biological evaluation and in silico studies. (1st January 2022) - Alqahtani, Ali S.; Ghorab, Mostafa M.; Nasr, Fahd A.; Ahmed, Mohammad Z.; Al-Mishari, Abdullah A.; Attia, Sabry M.
Abstract: We synthesised a new series of sulphonamide-bearing quinazolinone derivatives 5-18 and evaluated their in vitro cytotoxicity in various cancer cell lines (A549, HepG-2, LoVo and MCF-7) and in normal human cells (HUVEC). Compounds 6 and 10 exhibited the higher activity against all the cancer cell lines compared with 5-flourourcil as positive control. The ability of the most promising compounds 6 and 10 to induce cell cycle arrest and apoptosis in breast cancer (MCF-7) cells was evaluated by flow cytometry. Reverse transcriptase-polymerase chain reaction and western blotting were used to evaluate the expression of apoptosis-related markers. We found that the 2-tolylthioacetamide derivative 6 and the 3-ethyl phenyl thioacetamide derivative 10 exhibited cytotoxic activity comparable to that of 5-fluorouracil as reference drug in MCF-7 and LoVo colon cancer cells. Cell cycle analysis showed a concentration-dependent accumulation of cells in the sub-G1 phase upon treatment with both compounds. The Annexin V-fluorescein isothiocyanate/propidium iodide assay showed that the compounds 6 and 10 increased the early and late apoptosis cell death modes in a dose-dependent manner. These compounds downregulated the expression of B-cell lymphoma-2 (Bcl-2), while increasing that of p53, Bcl-2-like protein 4, and caspase-7, at the mRNA and protein levels. Molecular docking of compounds 6 and 10 with Bcl-2 predicted them to show moderate − high binding affinity (6 : −7.5 kcal/mol, 10 : −7.9 kcal/mol) and interactions with key central substrate cavity residues. Overall, compounds 6 and 10 were found to be promising anticancer and apoptosis-inducing agents.